DEPRESSION SYMPTOMS RECOGNITION "STOP SUICIDE" IN ADOLESCENTS - Faida Annisa; Firdah Nur Hidayah; Gilang Nova Permatasari; Dominggus Songupnuan; Dina Syafirah; Putri Putu Rakman; Rif’atul Umami (Community Service Journal of Indonesia, 2019)
Health promotion activities on the Recognition of the Symptoms of Depression "Stop Suicide" in Junior High School of Al-Aziziyah is one form of community service in the form of counseling aimed at increasing students' knowledge about how to recognize depression symptoms which are frequent events that cause death. The implementation of these activities on November 27, 2019 took place at Junior High School of Al-Aziziyah, Kebonsari, Candi Sub-District, Sidoarjo. The target of this event was the students of Junior High School of Al-Aziziyah, Kebonsari, Candi Sub-District, Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for approximately 3 weeks before the activity is carried out, starting from determining the theme of counseling to submitting permits to the parties concerned. As a form of evaluation, the activity was attended by 27 students and 1 teacher, participants participated in the activity happily and looked very enthusiastic, health promotion activities could run on time and smoothly. Keywords: Depression symptoms, adolescent, health promotion.